Mendebat Wali Nanggroe: Tinjauan Sejarah dan Respons terhadap Qanun Aceh No. 10 Tahun 2019 Tentang Lembaga Wali Nanggroe - Imam Hadi Sutrisno; Yety Rochwulaningsih; Ahmad Muhajir; Sukirno Sukirno; T. Junaedi; Hanif Harahap; Aulia Rahman (Jurnal Sejarah Citra Lekha, 2022)
This article discusses historical criticism of revitalization the wali nanggroe position which is against the Law on Governing Aceh (UUPA). This article is written based on research using qualitative methods with a historical approach. The data used comes from a number of literature reviews related to the topic and interviews with several informants. This research proves that there was an error by the Acehnese elite in interpreting the position of wali nanggroe which was not known at all during the Sultanate of Aceh Darussalam. The figure of wali nanggroe has been revived without comprehensive historical research written to boost the popularity and support of the Acehnese people for the Free Aceh Movement (GAM). After the Helsinki MoU and the enactment of the UUPA, Acehnese elite groups associated with the Aceh Party (Partai Aceh) became sponsors of the Qanun No. 10, 2019 which gave the wali nanggroe excessive power, contravened the UUPA, and were not based on the facts of the Aceh Darussalam Sultanate which to be hailed.